Effect of Profitability, Leverage, Size, Capital Intensity, and Inventory Intensity toward Tax Aggressiveness - Ati Sumiati; Salma Mustika Ainniyya (AIBPM Publisher, 2021)
The goal of this research is to find out the effect of profitability, leverage, size, capital intensity, and inventory intensity towards tax aggressiveness. Quantitative approach has been used in this research and applied the multiple linear regression analysis. Tax aggressiveness is measured by Effective Tax Rate (ETR). Population in this study was manufacture, and property, building, real estate companies listed on Indonesia Stock Exchange (IDX) for the year of 2019 – 2020. Purposive sampling used as sampling technique and 135 samples were acquired. Data for this research is analysed using descriptive statistics, classical assumption test, multiple linear regression, hypothesis test, and coefficient of determination with the help of SPSS version 26. According to the finding of the research, profitability, leverage, size, and capital intensity partially has no effect on tax aggressiveness, while inventory intensity has an effect on tax aggressiveness. All the factors affect tax aggressiveness and contribute 11.6%.